Two new Brazilian species of Begonia (Begoniaceae) from Atlantic Coastal Forest - Jacques, Eliane De Lima (Phytotaxa, 2020)
Two new species of Begonia (Begoniaceae) from Brazil are described and illustrated. Begonia cunhambebii and Begonia lorenzii are narrow endemic species from Atlantic Coastal Forest, an area full of endemism and with huge species richness. Preliminary IUCN Red List assessments are provided for the species.